Ultrasonication effects on graphene composites in neural cell cultures - Dybowska-Sarapuk, Łucja; Sosnowicz, Weronika; Grzeczkowicz, Anna; Krzemiński, Jakub; Jakubowska, Małgorzata (Frontiers in Molecular Neuroscience, 2022)
Spinal cord injuries and neurodegenerative diseases, including Parkinson's, Alzheimer's, and traumatic brain injuries, remain challenging to treat. Nowadays, neural stem cell therapies excite high expectations within academia. The increasing demand for innovative solutions in regenerative medicine has drawn considerable attention to graphene materials. Their unique properties are increasingly used as cellular scaffolds, supporting cell adhesion and proliferation. The proper dispersion of the functional phase particles in the polymer matrix is crucial for obtaining high-quality coatings. The performed experiments allowed for an increase in the efficiency of the manufacturing process of heterophasic, while reducing the resistance of the produced layers. Due to the high conductivity and biocompatibility of the used GNPs, the coatings were successfully applied in neural cell electrostimulation. The spray coating technique allows for the efficient fabrication of highly-conductive coatings on a variety of substrates, especially on cell-culture substrates used for neural cell electrostimulation. The GNP coatings were then used for electrostimulation of mouse NE-4C neural stem cells. In this study, the authors investigated how the value of the stimulation voltage amplitude affects cell behaviour, in particular the number of cells. sinusoidal alternating current was used for stimulation. Three different values of stimulation voltage amplitude were investigated: 5, 10, and 15 V. It was noticed that a lower stimulation voltage amplitude had the most favorable effect on the stem cell count.